Ekstrakurikuler di Pesantren Moderen: Sebuah Upaya dalam Pembentukan Karakter Santri - Emawati Emawati; Istiqamahtul Masyitah (DAYAH: Journal of Islamic Education, 2022)
Private Islamic Boarding Schools have received large audiences. Most people regardless of their economic and social status send their children to Islamic boarding schools. There are reasons parents choose this kind of school over other types of school, one of which is the fact that this type of schooling offers a wide variety of extra-curricular activities. This study seeks to identify the roles of extracurricular in shaping students’ character in a particular boarding school. This qualitative multi-site case study interviewed the management of the boarding schools, teachers, and students. The data for the research was also revealed through observation of students’ activities during the extra-curricular program. Our research suggests that extra-curricular were believed to have shaped students’ characters. The extra-curricular program shape students to become more disciplined, develop time-management skill, become more independent, and develop students’ creativities and students’ critical thinking. Our findings also reveal that the extra-curricular activities were run at a specified time, which does not distract students’ schedule for main learning activities.